DIVERSITE ET STRUCTURE GENETIQUE DE SAROTHERODON MELANOTHERON (PISCES : CICHLIDAE) REVELEES PAR LES MICROSATELLITES - Yoboue, Ahou Nicole; Adepo-Gourene, Abouo Béatrice; Agnese, Jean-François; Laë, Raymond (European Scientific Journal, ESJ, 2014)
The genetic diversity and structure of the specimens of Sarotherodon melanotheron (220 specimens), representing two endemic subspecies of West Africa, Sarotherodon melanotheron melanotheron (158 individuals) and Sarotherodon melanotheron heudelotii (62 individuals), were studied using microsatellites markers. All the samples come from seven sites. Specimens of S. m. heudelotii were caught in two sites (Sibassor and Albreda) and those of S. m. melanotheron were from five sites (Grand- Lahou, Layo, Adiaké, Ayamé and Kétesso). Ten locus microsatellites (PrlI AC, PrlI GT, UNH 860, UNH 874, UNH 887, UNH 957, UNH 1003, Smelt1, Smelt2 and Smelt4) were analyzed for the whole samples. The seven sites of sampling gathered in three distinct populations that are population of S. m. heudelotiithose of S. m. melanotheron from Lake Ayamé (Ayamé and Kétesso) and those of S. m. melanotheron from lagoon environment (Grand- Lahou, Layo and Adiaké). The strongest genetic variability was observed with specimens of S. m. melanotheron of lagoon environment (A = 15,60 ; HO = 0,479 and HE = 0,618) and weakest with individuals of S. m. melanotheron of the Lake Ayamé (A = 7 ;HO = 0,393 and HE = 0,533). The study of the structure highlighted a significant genetic differentiation (P < 0,001) between the three populations. This differentiation was also revealed by the AFC which isolated the specimens from these various populations in orthogonal space. Moreover, a significant deficit in heterozygotes was observed within these three populations on all of the ten locus analyzed.